2022
DOI: 10.1021/acs.jmedchem.1c02007
|View full text |Cite
|
Sign up to set email alerts
|

Cov_DOX: A Method for Structure Prediction of Covalent Protein–Ligand Bindings

Abstract: A handful of molecular docking tools have been extended to enable a covalent docking. However, all of them face the challenge brought by the covalent bond between proteins and ligands. Many covalent drug design scenarios still heavily rely on demanding crystallographic experiments for accurate binding structures. Aiming at filling the gap between covalent dockings and crystallographic experiments, we develop and validate a hybrid method, dubbed as Cov_DOX, in this work. Cov_DOX achieves an overall success rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
(114 reference statements)
0
36
0
Order By: Relevance
“…Nonetheless, in a covalent virtual-screening study, a researcher may select a covalent-docking program that has been reported to achieve a high success rate for his specific receptor/residue target, ligand warhead or reaction types. Hence, as a guideline to aid the docking community in choosing an ideal covalent-docking program for their virtual-screening experiments, we survey studies that are focused on comparative evaluation of the "front runner" covalent-docking tools [ 94 ].…”
Section: Selecting An Ideal Covalent-docking Program For Virtual-scre...mentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, in a covalent virtual-screening study, a researcher may select a covalent-docking program that has been reported to achieve a high success rate for his specific receptor/residue target, ligand warhead or reaction types. Hence, as a guideline to aid the docking community in choosing an ideal covalent-docking program for their virtual-screening experiments, we survey studies that are focused on comparative evaluation of the "front runner" covalent-docking tools [ 94 ].…”
Section: Selecting An Ideal Covalent-docking Program For Virtual-scre...mentioning
confidence: 99%
“…Secondly, Wen et al assessed the performance of four covalent-docking programs (COVDOCK, MOE, ICM-Pro, and GOLD) by employing a dataset from the BCDE set, which consists of 330 diverse ligand scaffolds and 104 receptor targets [ 93 ]. Lastly, Wei and co-workers developed a hybrid covalent-docking method known as COV_DOX and compared its performance to the previously identified covalent-docking tools (MOE, ICM-Pro, COVDOCK, and GOLD) [ 94 ]. Although, COV_DOX was validated to have a higher performance rate than all other covalent-docking tools (MOE, GOLD, ICM-Pro, and COVDOCK), the hybrid method is considered "not feasible" for a virtual-screening experiment because of its very high computing time, which is as a result of its GSA (Generalized simulated annealing) quantum mechanical calculation method [ 94 ].…”
Section: Selecting An Ideal Covalent-docking Program For Virtual-scre...mentioning
confidence: 99%
See 3 more Smart Citations